Insight into Fintech Products and Services in India among Generation Z - Anand, Abhijeet; Himani, Himani; Gautam, Abhishek Kumar; Modi, Satish (International Research Journal of Business Studies, 2023)
The primary objective of this research is to establish a comprehensive comprehension of the attitudes harbored by Generation Z toward fintech products and services and to identify the influential factors shaping their adoption and utilization patterns. This study endeavors to provide valuable insights regarding the determinants impacting the adoption and usage of fintech within this demographic. To achieve this goal, a descriptive and exploratory research design was employed, drawing upon a sample comprising more than 200 respondents. The study offers an extensive analysis of the market landscape, key industry participants, and emerging trends that are reshaping the fintech sector. The research findings divulge that the variables such as technological compatibility, economic stability, and usage frequency have significant influence over Generation Z’s perception and willingness to embrace fintech. The results accentuate the pivotal role these factors play in shaping the level of acceptance and adoption of fintech technologies among this demographic.